Efficient Search for Equivalents at Your Fingertips – The Specialized Translator’s Dream - Orozco-Jutorán, Mariana (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
The limitations of current terminology tools for specialized translators may, to a large extent, be explained by the complexity of the search process involved in producing good quality translations in specialist domains. This paper introduces a new approach to the development of this kind of resources aimed at satisfying the specific needs of specialized translators. This change of paradigm is reflected in the development of a prototype tool designed for use in legal translation. The tool – for use in English-Spanish translations of technological law in the localization of End User License Agreements – incorporates a revised corpus, comparative law information, and a terminological database. The features and advantages of the terminological database proposed are described in detail. Focusing on the specific needs of translators of this type of texts, comments are included on the acceptability of different terminological options on the basis of comparative legal analysis in different translation scenarios. The incorporation of these comments is a distinctive feature of this new approach to the development of resources and provides a value-added service to translators. The prototype tool designed is intended to serve as a model for the future development of similar applications in any type of specialized translation, in any given field and language combination.